환기모드에 따른 주행 승용차내 검댕 농도 특성 - 이승복; 배귀남 (한국실내환경학회, 2006)
Vehicle drivers are subject to be exposed to high concentrations of airborne pollutants emitted from vehicles on roads. To investigate the indoor air quality of vehicles on roads, black carbon (BC) was measured inside a passenger car commuting between the residential area in southern Seoul and the Korea Institute of Science and Technology (KIST) in northern Seoul using a portable aethalometer. When the vehicular windows were closed, the ventilation mode was set to fresh air mode (or circulation mode) for a total of thirteen runs made during May 2005. When the windows were open, the analysis was made with the system turned off (for twelve runs in October 2005). The BC concentration depended on such parameters as spatial location, time of day, and ventilation mode. The average BC concentration measured on non-express ways was higher than those measured on express ways, inside KIST, and nearby the residential area for most runs. On circulation mode, the average BC concentration was 5.9±1.7 ㎍/㎥ in the afternoon or evening, which was similar to a 24-hr average BC concentration for ambient air at 200 m apart from a road in Seoul. In the case of fresh air mode, the average BC concentrations measured in the morning rush hour, in the afternoon or evening, and after midnight were 22.8±3.4, 15.9±7.7, 3.7 ㎍/㎥, respectively. The average BC concentrations measured with the vehicular window open were 31.9±9.2, 19.4±5.9 ㎍/㎥, respectively in the morning rush hour and in the afternoon or evening. These measured values were higher than those measured with the windows closed. The average BC concentrations inside a passenger car with a fresh mode operation or open-window driving were significantly higher than a 24-hr average BC concentration measured at 200 m apart from a road in Seoul.